Effects of hierarchical nursing management in patients with acute pulmonary embolism. (May 2023) - Li, Keye; Zhang, Haiyan; Song, Jiakun; Zhang, Zhufeng
Highlights: Investigation of hierarchical nursing management in acute pulmonary embolism patients. Hierarchical nursing management short rescue time, reduce complications, improve outcomes and nursing satisfaction. Hierarchical nursing management improve the nursing quality of nursing care. Abstract: Background: Acute pulmonary embolism (acute PE) is the most serious manifestation of venous thromboembolism. Hierarchical nursing management is an improved option for nursing, but no study that indicated the effects of hierarchical nursing management in patients with acute PE could be found. This study aimed to explore the effects of hierarchical nursing management on the quality of nursing care and the prognosis of patients with acute PE. Methods From January 2020 to January 2022, 92 patients with acute PE were recruited and divided into the study group and the control group. The study group was designated with our hierarchical nursing care and the control group was designated with a conventional nursing care. The data of general characteristics, nursing quality, the improvement of clinical symptoms, the job satisfaction of nursing was collected and compared. Results The door-to-needle time, the thrombectomy time and length of emergency staying the study group were shorter than those in the control group ( P  < 0.005). The rate of complications in the study group was lower than that in the control group ( P  = 0.158). The scores of the nursing quality and the nursing satisfaction levels in the study group were remarkably higher than that in the control group. Conclusion For acute PE patients, the using of hierarchical nursing management can shorten the rescue time, reduce the rate of complications and improve the nursing quality of nursing care.